2022
DOI: 10.1155/2022/6884947
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Spherical Composite CMC-LTO-EGDE-ME for Lithium Recovery from Geothermal Water

Abstract: In this study, ethylene glycol diglycidyl ether (EGDE) and melamine (ME) were used to prepare a spherical composite material CMC-LTO-EGDE-ME through the strategy of cross-linking reaction of biodegradable sodium carboxymethyl cellulose (CMC) with Li2TiO3 (LTO) to improve the cycle stability of the adsorption-desorption for lithium recovery. In the geothermal water at 333.15°K, the adsorption capacity of the spherical composite adsorbent for lithium-ion is 12.02 mg/g, and the adsorption equilibrium time is 8 h.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…Ultradisperse titanium carbide powders produced at Shanghai Feiyan Industrial Development Co., Ltd. were selected. The electron microscopic method was used during research, and the JSM-IT200 (JEOL, Japan) scanning electron microscope of the "Uzbekistan-Japan Youth Innovation Center" was used [19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…Ultradisperse titanium carbide powders produced at Shanghai Feiyan Industrial Development Co., Ltd. were selected. The electron microscopic method was used during research, and the JSM-IT200 (JEOL, Japan) scanning electron microscope of the "Uzbekistan-Japan Youth Innovation Center" was used [19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…Crosslinking prior to granulation is anticipated to enhance the integrity of the LIS granules due to the mechanical stability of the crosslinked powdered sieve materials. composite materials is common [24,[47][48][49][50][51][52][53] and can be achieved either before or after granulation, with variable outcomes. Crosslinking prior to granulation is anticipated to enhance the integrity of the LIS granules due to the mechanical stability of the crosslinked powdered sieve materials.…”
Section: Preparation Of Lithium-ion Sieves: An Overviewmentioning
confidence: 99%
“…Regeneration studies using LiCl solution showed that the Li adsorption capacity of HTO/CA changed slightly after the first five adsorption-desorption cycles, with the final adsorption capacity being 22.95 mg/g. In another study, Xie et al [52] synthesized spherical composite LISs made of CMC-CLS, EGDE, melamine (ME), and LTO-based sieves with Li2TiO3 as the precursor. The multi-step crosslinked granules were made as follows: 1.5 g of Li2TiO3, 1.5 g CMC, and 100 mL of double deionized water (DDW) were added to a beaker and stirred at ambient temperature for about 6 h with sonication for several minutes to obtain a homogeneous mixture.…”
Section: Metal-based Liss Granulated With Cellulosementioning
confidence: 99%
See 1 more Smart Citation
“…Plenty of reserves identified for industrial development and exploited deposits in the Almalyk mining region in Uzbekistan, there are also non-traditional resources -waste from the enrichment and metallurgical processing of copper-molybdenum, lead-zinc and gold ore deposits. Technogenic wastes of mining (deposit), processing and metallurgical production represented by dump parent primary off-balance sulfide ore; and their oxidation products (balances, and off-balance mixed and oxidized ores), tailings of enrichment of copper-molybdenum and lead ores: slags; coca metallurgical production [6][7][8].…”
Section: Introductionmentioning
confidence: 99%